2019
DOI: 10.4103/sjamf.sjamf_1_19
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of lymphocyte-to-monocyte ratio in nephropathy of type 2 diabetes mellitus

Abstract: Background Inflammatory markers like interleukin-1, 6, and 8, transforming growth factor-β (TGF-β)1, and tumor necrosis factor-α have been found to be associated with diabetic nephropathy (DN), indicating that its pathogenesis may be inflammatory. These inflammatory markers are not routinely used, so, creating the need for easily and routinely done markers aim to enhance the prognostic process of diabetic microvascular complications. Lymphocyte-to-monocyte ratio (LMR), neutrophil-to-lymphocyte rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…In relation to the DN, values in present study were slightly lower than in the study performed in diabetic patients in Egypt, where in the group of patients with DN, NLR was 3.7 (normal value 1.7) and PLR 277.3 (normal value 108,3) in a somewhat younger population of participants (average age=57 years) then in present study. (Alsayyad MM et al 2019).The most comparable to present study findings are those reported by Akbas EM.et al (2016) at the University Hospital Ataturk in Anatolia. In contrast to other studies conducted in healthy participants, this one included patients who have been treated for some ill condition.…”
Section: Nlr and Plr In A Whole Group Samplesupporting
confidence: 92%
“…In relation to the DN, values in present study were slightly lower than in the study performed in diabetic patients in Egypt, where in the group of patients with DN, NLR was 3.7 (normal value 1.7) and PLR 277.3 (normal value 108,3) in a somewhat younger population of participants (average age=57 years) then in present study. (Alsayyad MM et al 2019).The most comparable to present study findings are those reported by Akbas EM.et al (2016) at the University Hospital Ataturk in Anatolia. In contrast to other studies conducted in healthy participants, this one included patients who have been treated for some ill condition.…”
Section: Nlr and Plr In A Whole Group Samplesupporting
confidence: 92%
“…LMR has been touted as the next surrogate inflammatory marker in diabetic nephropathy and this may be because lymphocytes are the mainstay of chronic inflammation. 17 But contrary to literature, in early T2D and in PDM, there was a definite decrease in LMR. As it is not a scenario of chronic inflammation in our subjects, lymphocytes are not dominating but instead in early metabolic disorders monocytes seem to be driving the LMR ratios as also evidenced by the significantly higher AMC values.…”
Section: Demographicsmentioning
confidence: 68%
“…Monocytes, part of innate immune system, present antigens to lymphocytes, part of adaptive immune system. 17 There was no significant correlation of any WBC or WBC derived parameters with Fasting Glucose levels. AMC showed significant but very weak correlation with 1hrPG, 2hrPG.…”
Section: Annals Of Tropicalmentioning
confidence: 77%
See 2 more Smart Citations